2022
DOI: 10.1101/2022.12.18.520962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of stereocilia length during development of hair bundles

Abstract: Assembly of the hair bundle, the sensory organelle of the inner ear, depends on differential growth of actin-based stereocilia. Separate rows of stereocilia, labeled 1 through 3 from tallest to shortest, lengthen or shorten during discrete time intervals during development. We used lattice structured illumination microscopy and surface rendering of mouse apical inner hair cells to measure stereocilia dimensions during early postnatal development; these measurements revealed a sharp transition at postnatal day … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 102 publications
(245 reference statements)
2
12
0
Order By: Relevance
“…By contrast, EPS8 shifted from having most labeling at row 1 tips in Ush1g bw /+ bundles (arrow in Figure 7C) to nearly identical levels at both row 1 and 2 tips in Ush1g bw/bw bundles (double arrow in Figure 7D). This broadened distribution of EPS8 resembled that seen in Pcdh15 av3J/av3J and Cdh23 v2J/v2J mutants 31 . MYO15A showed a similar altered distribution; while most MYO15A was found at row 1 tips in Ush1g bw /+ bundles (Figure 7E), its overall level was reduced in Ush1g bw/bw bundles and it was evenly distributed between rows 1 and 2 (Figure 7F).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…By contrast, EPS8 shifted from having most labeling at row 1 tips in Ush1g bw /+ bundles (arrow in Figure 7C) to nearly identical levels at both row 1 and 2 tips in Ush1g bw/bw bundles (double arrow in Figure 7D). This broadened distribution of EPS8 resembled that seen in Pcdh15 av3J/av3J and Cdh23 v2J/v2J mutants 31 . MYO15A showed a similar altered distribution; while most MYO15A was found at row 1 tips in Ush1g bw /+ bundles (Figure 7E), its overall level was reduced in Ush1g bw/bw bundles and it was evenly distributed between rows 1 and 2 (Figure 7F).…”
Section: Resultssupporting
confidence: 55%
“…Homozygous null mutations in Cdh23 and Pcdh15 lead to altered distribution of proteins that concentrate at the tips of row 1 stereocilia in postnatal hair bundle development 31 . While localization of GPSM2 and GNAI3 was only modestly affected, EPS8 shifted from being primarily found at row 1 tips to being equally distributed between row 1 and 2 tips.…”
Section: Discussionmentioning
confidence: 99%
“…6D). This broadened distribution of EPS8 resembled that seen in Pcdh15 av3J/av3J and Cdh23 v2J/v2J mutants 28 . MYO15A showed a similar altered distribution; while most MYO15A was found at row 1 tips in Ush1g bw /+ bundles (Fig.…”
Section: Resultssupporting
confidence: 52%
“…While localization of GPSM2 and GNAI3 was only modestly affected, EPS8 shifted from being primarily found at row 1 tips to being equally distributed between row 1 and 2 tips. We also showed that CDH23 and PCDH15 play an underappreciated role in coordinating the lengths of adjacent stereocilia 28 . Row 1 proteins showed similar altered distribution in Ush1g bw/bw , and adjacent stereocilia lengths were less coordinated, albeit not as profoundly disrupted as in Cdh23 v2J/v2J and Pcdh15 av3J/av3J hair cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation